PENGARUH COOPERATIVE LEARNING TIPE JIGSAW TERHADAP HASIL BELAJAR DAN MOTIVASI MAHASISWA - Supriyadi Supriyadi; Aris Setyawan (STIKes Surya Global Yogyakarta, 2016)
Background: Learning outcomes have an important role in the learning process that can be used as a reflection by teachers on the techniques used in teaching. Conventional teaching phenomenon is still frequently used, this causes students to be less active in the learning process. Innovative learning models should be applied so that interpersonal relationships between students, cooperative skills, and student self-confidence can be developed. Cooperative Learning Jigsaw type is one of the innovative learning methods that involve students in the learning process. There are five fundamental elements of cooperative jigsaw learning that can improve students' interpersonal skills, motivation and self-esteem. Objective: To know the influence of cooperative learning learning method to learning result and student motivation Stikes Surya Global Yogyakarta.Method: The research method used in this research is quantitative research with quasy experimental design, and pretest-posttest approach with control group. The sample of this research is second year student of STIKES Surya Global. Insrument using questionnaire and MCQ which then result analyzed by using Mann-Whitney test with value α 0,05.Results: The results showed that there were significant differences between the intervention group and the control group after intervention learning cooperative learning method with P 0.000 for cognitive learning result variable and P value 0.000 for motivation variableConclusion: There is influence of applying cooperative learning jigsaw method toward result of learning and motivation of study student S1 Study Program of Nursing STIKes Surya Global YogyakartaKeywords: Motivation, Learning Outcomes, Cooperative learning